Building services design for energy efficient buildings - Tymkow, Paul; Tassou, Savvas; Kolokotroni, Maria; Jouhara, Hussam (New York : Routledge, 2020)
"This book provides a contemporary introduction and guide to building services design, for students and practitioners alike"--
OCLC-licensed vendor bibliographic record.
Keywords: Sustainable buildings -- Design and construction; Architecture and energy conservation; ARCHITECTURE / Interior Design / General